Resurrection of Proteocephalus sagittus (Grimm, 1872) (Cestoda: Proteocephalidea) based on morphological and molecular data - Scholz, Tomás; Skeríková, Andrea; Hanzelová, Vladimíra; Koubková, Bozena; Barus, Vlastimil (Systematic parasitology, 2003)
This paper presents a redescription of the proteocephalidean cestode Proteocephalus sagittus (Grimm, 1872) based on freshly collected specimens from the type-host, the stone loach Barbatula barbatula (L.) (family Balitoridae), from the Czech Republic. This species has recently been synonymised with P. torulosus (Batsch, 1786), a parasite of cyprinid fishes in the Holarctic Region, but it differs in the following characters: (i) scolex morphology (scolex rounded, with more apically situated suckers and lacking longitudinal wrinkles in P. sagittus versus large and club-shaped, with more laterally situated suckers and longitudinal wrinkles in P. torulosus); (ii) position of the vagina (opens anterior to the cirrus-sac in P. sagittus versus overlapping its distal region dorsally in P. torulosus); (iii) length of the cirrus-sac (shorter in P. sagittus); (iv) osmoregulatory canals (more distinct and situated more laterally, but almost indistinguishable and more medial in P. torulosus); and (v) sequences of the partial 18S rRNA (V4 region - 96.9% similarity) and 5.8S-ITS2 genes (65.9% similarity). P. pamirensis Dzhalilov & Ashurova, 1971, a poorly described species from the Tibetan stone loach Noemacheilus stoliczkai[= Tryplophysa stoliczkae (Steindachner)] in Tadjikistan, is synonymised with P. sagittus.
Keywords: Polymerase Chain Reaction; Base Sequence; molekulární sekvence - údaje; sekvenční seřazení; zvířata; RNA, Ribosomal, 18S; DNA, Helminth; mikroskopie elektronová rastrovací; polymerázová řetězová reakce; RNA ribozomální 18S; Cestoda; Animals; Molecular Sequence Data; Female; DNA helmintů; Male; ženské pohlaví; Sequence Alignment; Cypriniformes; mužské pohlaví; Microscopy, Electron, Scanning; sekvence nukleotidů; máloostní